Natural and Artificial Fiber-Reinforced Composites as Renewable Sources - Günay, Ezgi (IntechOpen, 2018)
Nano- and micro-sized natural fibers of vegetable origin are fully biodegradable in nature. However, the nano- and micro-sized synthetic fibers are fully man-made. Fiber-reinforced composites composed of stiffened fiber and matrix are well-known engineering materials. Fiber-reinforced materials have been used in industrial production. Natural fibers can be obtained from many sources in nature such as wool, sisal, ramie, kenaf, jute, hemp, grass, flax, cotton, coir, bamboo and abaca, banana, and sugarcane bagasse. Artificial fibers have been produced from more stiff materials such as glass, single-walled carbon nanotubes, double-walled carbon nanotubes, carbon, aramid, boron and polyethylene (PE). The cyclic reusability of materials is an important qualification in protecting the environment from waste pollution. Three important factors can be mentioned in terms of material properties in the recycling process. The first factor is "the rate of cyclic usage," the second one is "less material loss in each recycle," and the last one is "the role of waste products in the self-renewal of ecosystem." In engineering area, the usage of waste materials has taken into account in production of composite materials. The use of waste materials as particulate-type composite production is also possible in the industry. Fiber-reinforced materials can be grouped into two categories: "the natural fiber-reinforced materials" and "the artificially produced fiber-reinforced materials." Finally, we conclude that this book consists of mainly summarized three subject headings within the two specific book subsections : The first group contains the main subjects related to the natural and artificial fibers obtained by literature review; second, experimental and numerical studies are made in order to perform the necessary arrangements in the production stages and to establish a decision mechanism on the specification of the technical properties of the fiber-reinforced composites. The third group of studies focused on the use of sustainable bio-composites and recycled textile wastes as reinforcements in construction.